1997
DOI: 10.1113/expphysiol.1997.sp004021
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of several opioids on cardiac muscle

Abstract: SUMMARYThe objective of the experiments was to investigate the cellular basis of the inotropic effect on myocardium of several opioids which have been implicated in producing cardiotoxic effects in human poisioning. Opioids exerted negative inotropic effects, with half-maximal concentrations between 10 /LM (dextropropoxyphene) and 118 /,M (pethidine); all agents reduced the magnitude of the intracellular Ca2+ transient and the L-type Ca2+ current, ICa, over a similar concentration range to that which reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Furthermore, morphine perfusion significantly reduced contractile force and shortened survival of the perfused heart despite a significant reduction in oxygen consumption. The negative inotropic and chronotropic actions of morphine and other opioids have been reported previously (11,12,29,33), and they are thought to be mediated by ␦-or -opioid receptors (3) or nonopioid receptors (33). Reports of positive inotropic action of morphine in intact animals are thought to be the result of sympathoadrenal discharge (30).…”
Section: [ 3 H]ne Uptake In Cardiac Synaptosomesmentioning
confidence: 99%
“…Furthermore, morphine perfusion significantly reduced contractile force and shortened survival of the perfused heart despite a significant reduction in oxygen consumption. The negative inotropic and chronotropic actions of morphine and other opioids have been reported previously (11,12,29,33), and they are thought to be mediated by ␦-or -opioid receptors (3) or nonopioid receptors (33). Reports of positive inotropic action of morphine in intact animals are thought to be the result of sympathoadrenal discharge (30).…”
Section: [ 3 H]ne Uptake In Cardiac Synaptosomesmentioning
confidence: 99%
“…However, its cardioprotective effect is known to be due to the activation of d-receptors 26,27 . Studies have shown that opioids like dextropropoxiphene, pethidine and leucine enkephalin reduce I Ca-L but only the inhibition induced by d-receptor agonist (leucine enkephalin) was blocked by naloxone 28,29 . The effects of tramadol on other ionic currents also suggest a direct effect on L-type Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 99%
“…13 DP also exerts a negative inotropic effect by its blockage of the inward calcium current. 14 Moreover, DP and NP dilate the systemic and coronary vascular beds. 10 The clinical use of naloxone to reverse DP cardiotoxicity is still being discussed.…”
Section: Casementioning
confidence: 99%